Early vascular parameters in the micro- and macrocirculation in type 2 diabetes - Kannenkeril, Dennis; Bosch, Agnes; Harazny, Joanna; Karg, Marina; Jung, Susan; Ott, Christian; Schmieder, Roland (Cardiovascular Diabetology, 2018)
BACKGROUND: Diabetes converts from a metabolic disorder into a predominantly vascular disease, once its duration extends over several years or/and when additional cardiovascular risk factors such as hypertension coexist. In a cross-sectional analysis we analyzed various vascular parameters in the renal, retinal and systemic circulation, with the goal to identify which vascular parameter of early organ damage is the earliest that can be clinically detected. METHODS: In 111 patients with type 2 diabetes (T2DM) (off any anti-diabetic medication for at least 4 weeks) and 54 subjects without T2DM we compared various parameters of early vascular remodeling in the same patient: urinary albumin creatinine ratio ([UACR], early morning spot urine) and estimated glomerular filtration rate (eGFR), retinal capillary flow (RCF) and intercapillary distance (ICD) as parameters of capillary rarefaction, wall-to-lumen ratio (WLR) of the retinal arterioles [all assessed by Scanning Laser Doppler Flowmetry], and central systolic pressure (cSBP) and central pulse pressure (cPP) [measured by pulse wave analysis, Syphygmocor] both reflecting vascular stiffness of large arteries. RESULTS: Compared to subjects without T2DM, patients with T2DM (diabetes duration: median 48 months, interquartile range 24-88 months) were older (59.8 ± 7.3 vs 43.4 ± 12.9 years, p < 0.001), more females (33.3 vs 20.4%, p < 0.001), but 24-h systolic and diastolic blood pressure did not differ between the two groups. The analysis adjusted for age, gender and cardiovascular risk factors revealed that ICD (23.9 ± 5.1 vs 20.8 ± 3.5 µm, p value = 0.001) and cPP (41.8 ± 11.7 vs 34.8 ± 10.6 mmHg, p value < 0.001) were significantly higher and eGFR (91.7 ± 9.9 vs 95.9 ± 17.3 ml/min/1.73 m2, p value < 0.001) was significantly lower in patients with T2DM than in subjects without T2DM. CONCLUSION: These data suggest that at similar blood pressure capillary rarefaction in the retinal circulation (ICD), decreased eGFR in the renal circulation and increased central pulse pressure (cPP) of large arteries are earlier detectable than other vascular remodeling parameters of the micro- (WLR, RCF, UACR) and macrocirculation (cSBP) in patients with T2DM. Trial registration Trial registration number: NCT02471963, Date of registration: June 15, 2015, retrospectively registered; Trial registration number: NCT01319357, Date of registration: March 21, 2011, retrospectively registered; Trial registration number: NCT02383238, Date of registration: March 9, 2015, retrospectively registered; Trial registration number: NCT00152698, Date of registration: September 9, 2005, prospectively registered; Trial registration number: NCT00136188, Date of registration: August 26, 2005, prospectively registered.
EVALuna2:35230